ZNACZENIE FINANCIAL SERVICES ACTION PLAN DLA BUDOWY WSPÓLNEGO RYNKU FINANSOWEGO W UNII EUROPEJSKIEJ - Kowalak, Tomasz (Wydział Prawa i Administracji UAM, 2003)
A Single Financial Market has long been an objective of the European Union. Despite the progress made in integration of financial markets in previous years, there is still a long way to travel. Differences in legal systems, differences in taxation, political and cultural barriers are the main obstacles in this context. To solve all the problems that hinder the benefits of fully integrated financial markets, in May 1999 the European Commission adopted the Financial Services Action Plan (FSAP). Financial Services Action Plan covers a vast area of financial activity and comprises 42 separate measures that are designed to complete the legislative framework for the internal market in financial services. These measures relate to both wholesale and retail markets and are categorized under a series of general action priorities (for example: establishment of common rules for integrated securities and derivatives markets, facilitating cross-border payments, etc.). FSAP also contains measures relevant to the prudential supervision of an integrated financial system, as well as measures that are designed to improve the general conditions for financial efficiency (corporate governance, taxation). All measures should be adopted and transplanted into national laws of the Member States by 2005. By June 2003, 34 out of 42 original measures had been finalized while the remaining 9 are being negotiated. The commitment of the European governments to implement the assumptions of a single financial market is substantial. Despite the adoption of 34 measures of FSAP, some barrier still remain. The main problem within this realm is related to the speed and quality of implementation of particular measures of FSAP. Nevertheless, it is hoped that the implementation of Financial Services Action Plan will help to achieve the single financial market or at least help to implement the majority of its assumptions.
THE ROLE OF FINANCIAL SERVICES ACTION PLAN IN BUILDING THE SINGLE FINANCIAL MARKET IN EUROPEAN UNION